2020
DOI: 10.4025/actascianimsci.v42i1.46029
|View full text |Cite
|
Sign up to set email alerts
|

Effects of in ovo injection of nano-selenium and nano-zinc oxide and high eggshell temperature during late incubation on antioxidant activity, thyroid and glucocorticoid hormones and some blood metabolites in broiler hatchlings

Abstract: This experiment was conducted to evaluate the effects of in ovo injection of nano-selenium (Nano-Se) and nano-zinc oxide (Nano-ZnO) and high eggshell temperature (EST) during late incubation on blood parameters of broiler hatchlings. A total of 750 fertile eggs, were weighed and randomly distributed among 5 treatment groups on each of 5 replicate tray levels. The injection was performed on 17 d of incubation. Treatments included of: 1) Eggs not injected and incubated at normal EST (control); 2) Eggs not inject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 45 publications
(71 reference statements)
0
11
0
Order By: Relevance
“…Antioxidant enzymes are responsible for elimination of reactive oxygen species, whereas MDA serves as an index of antioxidant status, is the end product of the oxidative stress (Shi et al 2011b ). Shokraneh et al ( 2020 ) showed that in ovo injection of nano-selenium (40 μg) and nano-zinc (500 μg) alleviated the negative effects of heat stress, induced by high eggshell temperature during late incubation, through boosting antioxidant activity and reducing oxidative stress (increased GSH-Px and SOD activity, while decreased corticosterone, cortisol, T4 and T3) in broiler hatchlings.…”
Section: Applications Of Nanoparticles As Feed Additives On Animal An...mentioning
confidence: 99%
See 1 more Smart Citation
“…Antioxidant enzymes are responsible for elimination of reactive oxygen species, whereas MDA serves as an index of antioxidant status, is the end product of the oxidative stress (Shi et al 2011b ). Shokraneh et al ( 2020 ) showed that in ovo injection of nano-selenium (40 μg) and nano-zinc (500 μg) alleviated the negative effects of heat stress, induced by high eggshell temperature during late incubation, through boosting antioxidant activity and reducing oxidative stress (increased GSH-Px and SOD activity, while decreased corticosterone, cortisol, T4 and T3) in broiler hatchlings.…”
Section: Applications Of Nanoparticles As Feed Additives On Animal An...mentioning
confidence: 99%
“…Dietary ZnONPs have shown to be beneficial in ameliorating the negative effects of heat stress (Ramiah et al 2019 ; Shokraneh et al 2020 ). Akhavan-Salamat and Ghasemi ( 2019 ) compared three sources of dietary Zn (Zn oxide, Zn-Methionine (Zn-Met), and Zn oxide nanoparticles – ZnONPs) and three doses of supplemental Zn (low: 20 mg/kg, adequate: 40 mg/kg, and high: 80 mg/kg of diet) to broiler chickens reared under heat stress beginning from 14 to 42 days.…”
Section: Metal Nanoparticles In the Nutrition Of Particular Animal Sp...mentioning
confidence: 99%
“…Because of these considerations, there are various strategies to mitigate the adverse effects of heat stress on animals, among them nanotechnology. Nanotechnology has rapidly expanded in many scientific fields, and the nanoscale exhibits attractive properties such as small size, large surface area, highly active surfaces, high catalysis efficiency, and vast adsorption capabilities [6]. By increasing nanoparticle surface area, nanoparticles have the potential to interact efficiently with the body, and their increased retention time in the gut and the reduction of intestinal clearance mechanisms may result in improved bioavailability and function [7].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, nanoparticles can improve growth performance, meat quality, digestion and metabolic or antioxidant enzymes, and mineral content in different tissues under physiological stress [8]. In the poultry industry, nanoparticles smaller than 100 nanometers, such as Ag, Se, Cu, Zn, and others, have been used [6,7,9]. According to our knowledge, no review has been performed to assess the positive effects of mineral nanoparticles in the poultry industry under heat stress.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, multiple areas have yet to be explored sufficiently in livestock physiology that have proven useful in humans and other model species, which may now be gaining some research attention. A few of these include investigations of the microbiotagut-brain axis and impacts on physiology including growth performance (Ming et al, 2021) and welfare (O'Callaghan et al, 2016;Kraimi et al, 2019); effective exploitation of organoids in basic research (Beaumont et al, 2021;Kar et al, 2021); and use of nano-technology for delivery of therapeutic compounds (Hill and Li, 2017;Shokraneh et al, 2020). Comprehensive bioinformatic analysis and interpretation of transcriptomic and metabolomic data collected from livestock tissues during normal development or critical disease states are also needed.…”
mentioning
confidence: 99%